Techno-Economic Study of Solar Panel Implementation as the Alternative Energy Source in Mataram City - Laras, Muhammad Inditiya Gegar; Farras, Muhammad Abiyyu (Asian Journal of Social and Humanities, 2025)
Mataram City, the capital of West Nusa Tenggara Province, has strong potential for solar energy development due to its favorable geographic and climatic conditions. Indonesia’s commitment to reducing greenhouse gas (GHG) emissions by 41% by 2030, along with the province’s net zero emission goal by 2050, underscores the importance of renewable energy deployment. This study aims to evaluate the technical and economic feasibility of implementing solar panels as an alternative energy source in Mataram City and to assess their contribution to GHG emission reduction. The analysis uses RETScreen software with secondary data from NASA’s Surface Meteorology and Solar Energy (SSE) database. It covers resource assessment, cost analysis, and financial indicators including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Levelized Cost of Electricity (LCOE). Mataram receives an average daily solar radiation of 5.4 kWh/m²/day, with consistent potential throughout the year. The financial analysis shows that the project is technically feasible and economically viable, supported by positive NPV and IRR values, and provides significant contributions to GHG reduction. Solar panel implementation in Mataram City is proven to be feasible in technical, financial, and environmental terms. The findings serve as a valuable reference for local governments in formulating sustainable and low-carbon energy strategies.